Improved reproductive performance through edible bird’s nest and its ameliorating properties in lead acetate toxicity of reproductive system in female rats - Albishtue, Abdulla Aaid Hadi (2018)
Edible Bird’s Nest (EBN) is an animal product from the salivary secretion of male swiftlet birds (Aerodramus fuciphagus and Aerodramus maximus). It is traditionally consumed Asians for its nutritional and medicinal values. Although enhancing reproductive functions is among the traditionally claimed benefits of consuming EBN there is a dearth of scientific evidence in this regard. The aims of this study were to determine the effects of EBN supplement on the reproductive functions of cycling female rats, on pregnant female rats, and subsequently to evaluate the ameliorating effect of EBN supplement against toxic effect of lead acetate (LA) to the female reproductive system and pituitary gland. To address the first objective of this study (evaluation of the effects of EBN supplement on the ovarian, uterine and pituitary gland activities of cycling female rats), histomorphometric analysis and assessment of expressions of epidermal growth factor (EGF), its receptor (REGF), proliferating cell nuclear antigen (PCNA), vascular endothelial growth factor (VEGF), steroid receptors on ovaries and uteri as well as measurement of steroid hormones, prolactin (P) and growth hormone (GH) from plasma, were employed. Twenty four Sprague Dawley rats were divided into 4 equal groups (n=6): G1 as control group while G2, G3 and G4 were treated groups with EBN at graded concentrations of 30, 60 and 120 mg/kg of body weight per day respectively for 8 weeks. The EBN was administered orally using gavage tube. At the proestrus stage all rats were sacrificed to remove ovaries, uteri, pituitary glands and liver for histological and immunohistochemical analyses. Results showed significant ovarian structural and histological changes such as numbers of interstitial cells and growing follicles in EBN treated groups, with significant increase in endocrine cells and vascularization of pars distalis of the pituitary glands as well as increased uterine epithelium and number of uterine glands. There was no histomorphological change of liver among groups. Samples from G3 and G4 demonstrated significant expressions of EGF on ovarian surface epithelium, interstitial cells, uterine surface epithelium and uterine stromal cells as well as higher expressions of PCNA and VEGF, and estrogen receptor (E2R) compared with G1 and G2. No staining for progesterone receptor (P4R) was observed in the treated groups. In addition, immunohistochemistry of the uterus showed significantly higher expressions of EGF, REGF, PCNA, E2R and P4R (p < 0.05) in G4. The plasma levels of estrogen (E2) (ng/mL) and progesterone (P4) (ng/mL) in G4 (18000±1786; 168±17) were significantly higher than G3 (11000±3670; 84.04±9.56), G2 (6300±1566; 63.66±9.06), and G1 (1100±143; 50.03±4.18). Moreover, concentrations of prolactin P and GH were observed to be significantly higher (p < 0.05) in G4. These findings suggest that EBN supplement enhances ovarian follicular growth, uterine structures, expressions of E2R, P4R EGF, REGF, VEGF, and PCNA and subsequent rise in plasma E2, P4, P and GH levels. These imply the strong enhancing effect of EBN on the reproductive system of cycling female rats. In order to determine effect of EBN supplement on embryo implantation rate and associated changes in the uterus, plasma steroids and oxidative stress biomarkers (2nd objective), a total 24 female adult rats underwent similar treatment for 8 weeks. In the last week of treatment, however, intact fertile male rats were introduced into each group (three per group) with proestrous stage overnight for mating. On day 7 postmating (expected days of implantation; peri- and post-implantation), the animals were sacrificed for assessment of implantation rate, histological and electron microscopic examination of the uterus, oxidative stress biomarkers (OSB) and antioxidant (AO) assay, GH, P, steroid hormones analysis, and expressions of steroid receptors, EGF, REGF, PCNA, and VEGF on the uterus. Results showed that as the concentrations of EBN increases, the pregnancy rate, embryonic implantations rate and development of microvilli with pinopodes in uterine epithelium were also increased. There was an increased level of superoxide dismutase (SOD) and total antioxidant capacity (TAC) (p < 0.05) in the G4, with lower (p < 0.05) concentrations of thiobarbituric acid reactive substance (TBARS) compared to control. All results of the hormones assay and immunohistochemistry showed significantly higher concentrations and expressions of steroid receptors, EGF and REGF, PCNA, and VEGF (p < 0.05) in G4 compared to the other groups. These findings imply that almost all the factors important for embryo implantation and development are enhanced in concentrations and expressions with EBN supplement in a dose dependant manner subsequently resulting in increased embryo-implantation and pregnancy rate. The last objective in the present study was to evaluate the protective effect of EBN supplement to the reproductive system (ovaries and uteri) and pituitary glands of female rats against lead acetate (LA) toxicity. LA is a toxic compound that has harmful effects on the female reproductive system such as altered uterine and ovarian histology, size and function, and low oestrogen production. There were five treatment groups: Group 1 - control (C) was given normal saline, group 2 (T0) was administered with LA (10 mg/kg bwt), while groups 3 (T1), 4 (T2) and 5 (T3) were given LA (10 mg/kg bwt) and graded concentrations of 30, 60, and 120 mg/kg bwt of EBN, respectively. Rats were euthanized at day 30 for collection of blood plasma, ovary and uterus. Organ tissues were fixed in 10 % buffered formalin and subjected to histological analyses and immunohistochemistry for expression of steroid receptors, EGF and REGF, PCNA, and VEGF on the ovary and uterus. Plasma was used to determine concentrations of E2, oxidative stress biomarker (OSB) and antioxidant (AO). Results showed that the level of E2 was lower (p < 0.05) in the T0 group while the T3 group had the highest E2 concentration. There was a decreased level of SOD and TAC (p < 0.05) in the T0 group and an increased SOD and TAC level in the T3 group, while T0 had higher (p < 0.05) concentrations of TBARS compared to treated groups, indicating oxidative stress. There was a reduced number of primordial follicles and increased numbers of atretic follicles in the ovary as well as significant damage in the uterus as evidenced by reduction in uterine glands and decrease in height of columnar cells in the T0 group compared with the treatment groups. Moreover, histological examination of pituitary gland of LA exposed rats without EBN supplement showed degenerative changes in endocrine cells of pars distalis such as non-uniform arrangement of the cells and decrease in cell number and size. Interestingly, histological examination of pituitary glands, ovaries and uteri of EBN treated groups showed significant protection as evidenced by a significant increase in endocrine cells of pars distalis, growing follicles and CL, but decrease in number of atretic follicles on ovaries as well as increase in uterine glands and height of columnar cells. All results of immunohistochemistry showed significantly higher expression of steroid receptors, EGF, PCNA, and VEGF (p < 0.05) in T3 compared to other groups. This part of the experiment reaffirmed the detrimental effects of LA on the reproductive system and revealed novel findings on the ameliorating effect of the oral supplementation of EBN against LA toxicity damage to the reproductive system, achieved best at 120mg/kg body weight. In general, this study suggests that EBN supplement enhances functions of the pituitary gland, ovary, uterus, expression of steroid receptors, EGF, REGF, VEGF, and PCNA on ovaries and uteri along with a rise in serum E2, P4, P and GH levels. Moreover, EBN has showed a promoting effect on fertility indexes by increasing pregnancy and embryo implantation rates. Furthermore, the present study revealed that EBN supplement at oral dose of 60 – 120mg/kg body weight is capable of protecting and preventing alterations in the pituitary gland and the reproductive system due to lead toxicity through an integrated mechanism of maintaining antioxidant – reactive oxygen species (ROS) balance. Overall findings of the present study provide scientific evidence in support of the traditional claim of EBN’s benefit to reproduction and being one of the reasons for consumption among humans.